RELEVANSI PEMBARUAN PENDIDIKAN ISLAM MUHAMMAD ABDUH TERHADAP TANTANGAN MODERASI BERAGAMA DALAM PEMBELAJARAN PAI - Yesi Yesi; Khairinnisa Zahrawani; Nur Apriyanto; Ririn Dwi Wiresti (STKIP Pesisir Selatan, 2026)
Although studies on the reform of Islamic educational thought have been widely conducted, research that specifically examines the relevance of the ideas of Muhammad Abduh for the development of Islamic Religious Education (PAI) learning in the digital era remains limited. This study aims to analyze the epistemological concept of Islamic education proposed by Abduh and explore its relevance in constructing an integrative, moderate, and contextual model of PAI learning. This research employs a qualitative approach using a library research method. Primary data sources are derived from Abduh’s works, such as Risalah al-Tauhid and Tafsir al-Manar, while secondary sources include books and scholarly articles discussing Islamic educational thought and religious moderation. Data were collected through documentation techniques and analyzed using a descriptive-analytical approach, involving stages of concept identification, interpretation, and conceptual synthesis. The findings reveal that Abduh’s epistemology of Islamic education emphasizes the integration of reason and revelation as the primary foundation for the development of knowledge. This integration produces an educational paradigm that balances rationality, spirituality, and moral values in the learning process. Furthermore, the concept of religious moderation embedded in his thought provides a significant foundation for building inclusive and dialogical Islamic education.